Histone Methyltransferases as Therapeutic Targets for Kidney Diseases - Yu, Chao; Zhuang, Shougang (Frontiers in Pharmacology, 2019)
Emerging evidence has demonstrated that epigenetic regulation plays a vital role in gene expression under normal and pathological conditions. Alterations in the expression and activation of histone methyltransferases (HMTs) have been reported in preclinical models of multiple kidney diseases, including acute kidney injury, chronic kidney disease, diabetic nephropathy, polycystic kidney disease, and renal cell carcinoma. Pharmacological inhibition of these enzymes has shown promise in preclinical models of those renal diseases. In this review, we summarize recent knowledge regarding expression and activation of various HMTs and their functional roles in some kidney diseases. The preclinical activity of currently available HMT inhibitors and the mechanisms of their actions are highlighted.